Missionary translators : translations of Christian texts in East Asia - Kiaer, Jieun; Bianchi, Alessandro, (Japanese scholar); Falato, Giulia; Jolliffe, Pia; Mino, Kazue; Yu, Kyungmin (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Exploring the history of missionary translation of Christian texts in East Asia, Missionary Translators offers a comparative perspective between the features of East Asian languages and the historical context of the translation. Focusing on the Bible and Christian theological works, it looks at the intersection of linguistics, translation studies, and history. This book discusses the real-life challenges faced by missionary translators in producing Christian texts in East Asian languages. Students, historians, scholars and those interested in the study of East Asian cultures or translation will find this book to be an insightful and invaluable resource"--
Keywords: Bible. -- Versions; Bible. -- Versions; Bible. -- Versions; Translating and interpreting -- East Asia -- History; Missionaries -- East Asia -- History; FOREIGN LANGUAGE STUDY / Chinese; FOREIGN LANGUAGE STUDY / Korean; LANGUAGE ARTS & DISCIPLINES / Journalism